Functional Characterization of Eyes with Diabetic Macular Edema, submitted to intravitreal anti-VEGF treatment - Domingos, Sérgio Pestana (2018)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina